Infantile Status Epilepticus & Mesial TLE - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The clinical and EEG characteristics of initial status epilepticus (SE) during infancy were studied in six patients seen in the emergency clinic between 1977 and 1988 at Tokyo Women's Medical University, Japan.